Pengaruh Media Film Frozen (2013) terhadap Kemampuan Menulis Teks Narasi Siswa Kelas VIII Sekolah Menengah Pertama Negeri 5 Medan - Nirma Devi Br Silaban (Jurnal Bahastra, 2026)
This study addresses the persistent challenge of improving students’ narrative writing ability in Indonesian language learning by integrating audiovisual media into classroom practice. It investigates whether the use of the film Frozen (2013) significantly enhances the narrative writing skills of eighth-grade students at Sekolah Menengah Pertama Negeri 5 Medan during the 2025–2026 academic year. Employing a quantitative approach with a quasi-experimental design, the study compares students’ writing performance before and after the intervention, involving both control and experimental groups. The findings reveal a substantial improvement in the experimental group, which achieved a mean score of 78.63 compared to 49.15 in the control group, indicating that the film-based learning approach outperforms conventional methods. The results confirm a statistically significant effect of using Frozen (2013) as a learning medium on students’ narrative writing skills. This study argues that audiovisual media, particularly films, can effectively stimulate students’ imagination, engagement, and linguistic competence, thereby contributing to more innovative and effective Indonesian language instruction.